08.49 Efficacy of an intensive 24-week physiotherapy programme in scleroderma patients – preliminary data from a single-centre controlled study. (1st March 2017) - Spiritovic, Maja; Smucrova, Hana; Oreska, Sabina; Storkanova, Hana; Cesak, Petr; Rathouska, Adela; Ruzickova, Olga; Mann, Herman; Pavelka, Karel; Senolt, Ladislav; Vencovsky, Jiri; Becvar, Radim; et al.
Abstract : Background: Involvement of skin and musculoskeletal system in systemic sclerosis (SSc) leads to loss of function, disability and reduced quality of life. Data on efficacy of non-pharmacologic care in SSc is very limited due to variety in studied interventions/outcomes. Objectives and methods: To address the limitations of existing studies, and evaluate the effect of a controlled, long-term (24-week intervention, 24-week follow-up), intensive (1 hour physiotherapy +0.5 hour occupational therapy twice weekly, and home-exercise for 0.5 hour 5x weekly), tailored physiotherapy program on function/impairment of hands/face, and quality of life/disability in cohorts with a substantial number of SSc patients. All patients fulfilled ACR/EULAR 2013 criteria, had skin involvement of hands/mouth, and were consecutively recruited between 2014–2016. At months 0, 3, 6, 12 all patients were assessed by a physician (physical history, mRSS, EUSTAR SSc activity score, Medsger severity score), and a physiotherapist blinded to intervention [validated measurements (dFTP-delta finger to palm, inter-incisor/inter-lip distance, grip strength using Baseline dynamometer ); tests (HAMIS-Hand Mobility In Scleroderma)], patients filled out PRO questionnaires (CHFS-Cochin Hand Function Scale, MHISS-Mouth Handicap In SSc Scale, HAQ, SHAQ, SF-36) and provided blood for routine laboratory analysis and biobanking. Normality of data was tested and inter-group analysis performed with 2-way ANOVA and intra-group analysis by Friedmann's test with Dunn's post hoc test. Results: 25 SSc patients (22 female/3 male, 14 lcSSc/11dcSSc, median of age 54.0 and disease duration 7.0 years, mRSS 12) were recruited into the intervention group (IG) and 29 patients into CG (25 female/4 male, 16 lcSSc/13 dcSSc, median of age 49.0 and disease duration 5.0 years, mRSS 11). Compared to observed statistically significant deterioration in CG over the period of m0-m6, we found statistically significant improvement in dFTP, grip strength, HAMIS, inter-incisor and inter-lip distance. Only numerical improvement in IG compared to numerical deterioration in CG, which have not reached statistical significance, were observed in patient reported outcomes (CHFS, MHISS, HAQ, SHAQ, SF-36). Conclusions: Our physiotherapy program not only prevented the natural course of progressive deterioration of function of hands/mouth (observed in CG), but led to a significant improvement in monitored parameters, which was clinically meaningful in a substantial proportion of patients. Acknowledgement: Supported by AZV-16–33574A.